SYNTHESIS OF CARBON DOTS (CDS) AND DETERMINATION OF OPTICAL GAP ENERGY WITH TAUC PLOT METHOD - Jumardin Jumardin; Akhiruddin Maddu; Koekoeh Santoso; Isnaeni Isnaeni (Universitas Negeri Gorontalo, 2021)
Carbon Dots (CDs) which have been synthesized using the laser ablation method show the presence of UV-Vis absorption in the wavelength range of 303 nm to 333 nm for absorbance and 495 nm to 503 nm for fluorescence. Changes in the time duration 1, 2, 3 hours of CDs resulted in changes in the optical energy gap. The optical energy gap valuesare distinguished by the type of indirect transition (n=2) is 3.40 eV (1 hour), 3.15 eV (2 hour), 2.85 eV (3 hour) and direct transition (n=1/2) is 2.58 eV (1 hour), 2.31 eV (2 hour), 1.70 eV (1 hour).